Prevalence and factors associated with gastroesophageal reflux disease among primary health care attendants at Abha city, southwestern Saudi Arabia - Mohammed A. Alsaleem; Nabil J. Awadalla; Shehata F. Shehata; Awad Saeed Alsamghan; Mohammed A. AlFlan; Marwan M. Alhumaidi; Mohamed S. Alwadai; Fahad S. Althabet; Mohamad S. Alzahrani; Safar A. Alsaleem; Ahmed A. Mahfouz (Elsevier, 2021)
Background: Gastroesophageal reflux disease (GERD) is an abnormal reflux of the gastric content into the esophagus. In Saudi Arabia the GERD prevalence is not recently well studied. Objective: To investigate the prevalence of gastroesophageal reflux disease and associated factors among attendants of primary health care centers (PHCCs) at Abha city, Saudi Arabia. Method: A descriptive cross- sectional study was performed using GerdQ as diagnostic tool for the GERD. The GerdQ consisted of six questions. Four questions were about the positive GERD predictors. The other two questions were about the negative GERD predictors. The scoring of GerdQ relies on the frequency of GERD symptoms during the last seven days. Using stratified random sample technique a representative sample was slected from the study PHCCs taking into conmsideration the relative catchment population in each center among adult males and females attending the selected PHCCs for any reason. Results: The present study included 320 persons. The study showed a prevalence of GERD of 67.8%. The prevalence of GERD with high impact on daily life (HIDL) was found to be 50%. By multiple logistic regression (enter method) only four significant independent factors associated with GERD were identified; being unmarried (aOR = 1.85, 95% CI:1.02-3.23); smoking (aOR = 2.11, 95% CI: 1.41-5.98), fast food intake (OR = 1.28, 95% CI:1.01-1.71), and subjective perception of stress (OR = 3.0, 95% CI:1.68-5.26). Conclusions: GERD is a public health problem among adults in the region. Community level awareness programs are recommended. Healthcare providers must be aware of community perceptions and practices.